Acute Cerebellar Ataxia and Lyme Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Child neurologists at Baskent University Faculty of Medicine, Turkey, report the case of a 5-year-old girl from the Mediterranean region of Anatolia with a 4-day history of progressive ataxia.